EXPLORING THE LEGAL FRAMEWORK FOR STALKING IN INDIA (International Journal of Food and Nutritional Sciences, 2022)
This comprehensive study delves deeply into the multifaceted legal framework governing stalking inIndia. It critically analyzes the effectiveness of existing legislation, including the Indian Penal Code andthe Criminal Procedure Code, in addressing and preventing this pervasive menace